Effects of the primary lung infection on outcomes in patients with severe ARDS treated with ECMO: a retrospective analysis - Mirus, Martin; Heubner, Lars; Brückner, Martin; Birkner, Thomas; Güldner, Andreas; Rand, Axel; Menk, Mario; Petrick, Paul Leon; Harb, Hani; Spieth, Peter Markus (Frontiers in Medicine, 2025)
IntroductionAcute respiratory distress syndrome (ARDS) requiring veno-venous extracorporeal membrane oxygenation (vvECMO) remains associated with high mortality. Whether etiology-based differentiation within infectious ARDS improves prognostic and therapeutic precision remains unclear. This study compared vvECMO-treated ARDS patients with different pulmonary infections to identify clinically relevant etiology-specific differences.MethodsThe retrospective single-center cohort study included adult patients who received vvECMO for severe infectious pulmonary ARDS between 2014 and 2021. Patients were categorized into Covid-19 (n = 48) and Non-Covid (n = 44). Clinical parameters, disease progression, treatment, and outcomes were compared. Cox and modified Poisson regression analyses identified predictors of ICU mortality.ResultsNon-Covid ARDS patients had greater disease severity at ECMO initiation, although mortality was lower: SOFA score (15.7 vs. 13.7; p = 0.003); PRESERVE score (3.73 vs. 2.73; p = 0.004). In Covid-19 ARDS, age ≥60 years (RR 1.62), early SOFA score worsening (RR 1.17), new renal replacement therapy (RR 1.60), and septic shock (RR 3.33) were associated with increased mortality, whereas these factors were not predictive in Non-Covid ARDS. Red blood cell transfusion was associated with reduced mortality in both groups (HR 0.96 and 0.95), while fresh frozen plasma transfusion increased mortality exclusively in Covid-19 ARDS (HR 1.09). A rising SOFA score within 5 days after ECMO initiation predicted mortality only in the Covid-19 cohort (RR 1.17).ConclusionEven within primary infectious pulmonary ARDS, substantial heterogeneity exists. The underlying infection critically affects the prognostic value of clinical parameters, organ dysfunctions, and scoring systems in vvECMO-treated patients. Considering ARDS etiology may improve risk stratification and guide individualized therapy.Trial registrationGerman Clinical Trials Register (DRKS00027856), https://drks.de/search/en/trial/DRKS00027856.